PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SENI RUPA DI SMP N 34 PADANG - Sofrizal Daswir, Dr. Ramalis Hakim, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2018)
This research was done based on the interest students of SMPN 34 Padang who still have low study results for the subject of culture and arts, especially on fine arts that aim to determine the effect of using Jigsaw technique of cooperative learning toward students’ study results of fine arts in SMPN 34 Padang.This research was experimental research with the type of quasi-experimental pretest-posttest control group design. The population was all fine arts students of SMPN 34 Padang. The sampling was using purposive random sampling technique. The data analysis is hypothesis test with t- test at significant level 0.05. The results of experimental class using Jigsaw technique of cooperative learning have higher study results than students at control class using conventional learning model.Keywords: Jigsaw type cooperative learning model and learning outcomes.